Diseño de un modelo de vivienda rural social sostenible, bioclimática para la vereda Espinal Bajo del municipio de Los Santos, Santander. (2021)
In this degree project, the design of a prototype of sustainable, bioclimatic social rural housing for the Espinal Bajo village of the municipality of Los Santos, Santander, was carried out. Which aims to respond to the housing deficit and the problem of unsatisfied basic services such as an adequate elimination of excreta.